Aliyeva Zulxumor Jabbor qizi THE ART OF PUBLIC SPEAKING AND ITS FEATURES - Zulxumor Alieva (Proceedings of The ICECRS, 2019)
In this article, the Art of public speaking and its features, public speaking as a special skill, art, in the form of a special unique ability of a person is reflected in the interpretation. On this case, both methodological and theoretical points were discussed by the author. Finally, received outcomes and shortcomings were stated to make further development.